Challenge of the Barons - Are, Lekan (University Press Plc, 2001)
When the much-loved achiever, Dr. Onaola Jungu, accepted an appointment as a professor of horticulture in Serti University, little did he know that he was going to meet eyeball to eyeball with bareface academic colonialism generated and nurtured in the guise of American economic aid to the poor African nation-Kato...
Keywords: Juvenile Fiction